PSMD11 and PSMD14 may serve as novel biomarkers for the prognosis of pancreatic ductal adenocarcinoma - Yang, Yan-Hui; Xing, Zhe-Hua; Wang, Hao; Zhang, Chi; Liu, Yu-Bo; Bai, Qian-Qian; Liu, Fang-Fei; Liu, Wei-Feng; Yang, Jun-Chuan; Li, Da-Huan; Fan, Hua (Frontiers in Oncology, 2025)
BackgroundThe ubiquitin proteasome system is involved in the regulation of cellular gene transcription and cellular receptor function through the degradation of proteins, thus affecting tumorigenesis and development. In this study, bioinformatics analysis revealed the expression of PSMD11 and PSMD14 in pancreatic ductal adenocarcinoma, which can be used as biomarkers for the prognosis of patients with PDAC. This study provides new targets for the prognostic assessment and targeted therapy of pancreatic ductal adenocarcinoma.MethodsThe expression levels and prognostic value of PSMD11 and PSMD14 in pancreatic ductal adenocarcinoma patients were analyzed using the GEPIA2, GEO, TCGA and GTEx databases, and the relationships between these expression levels and clinical case data and the survival and prognosis of patients with pancreatic ductal adenocarcinoma were analyzed. The effects of PSMD11 and PSMD14 on the malignant biological behaviors of pancreatic cancer cells, such as proliferation, migration and invasion, were investigated by in vitro experiments.ResultsBioinformatics analysis revealed that the expression levels of PSMD11 and PSMD14 mRNAs were significantly higher in pancreatic ductal adenocarcinoma (PDAC) tissues than in normal pancreatic tissues and that this high expression was correlated with a poor prognosis in patients with PDAC. Further evaluation of the expression of PSMD11 and PSMD14 and correlation of the results with the clinical characteristics and survival of patients with PDAC revealed that high expression of PSMD11 and PSMD14 was associated with lymph node metastasis, TNM grade, degree of differentiation, and poor prognosis in patients with PDAC. Knockdown of PSMD11 and PSMD14 significantly inhibited the proliferation, migration, and invasion ability of pancreatic cancer cells.ConclusionPSMD11 and PSMD14 are highly expressed in pancreatic ductal adenocarcinoma tissues and are correlated with the degree of malignancy of pancreatic ductal adenocarcinoma; thus, PSMD11 and PSMD14 can be used as potential prognostic biomarkers and therapeutic targets for PDAC patients.